How to make failure productive: Fostering learning from errors through elaboration prompts. (August 2019) - Loibl, Katharina; Leuders, Timo
Abstract: Research on conceptual change, learning from errors, and 'productive failure' suggests that elaborating on errors during instruction is crucial for learning in settings which put problem solving before instruction. To reveal the role of elaboration and comparison of errors, we investigated the effect of prompting students to engage in such cognitive processes: Students in all conditions first worked on an identical problem-solving activity (targeting the comparison of fractions) without prior instruction about the targeted concepts and procedures. In the subsequent instruction phase, students in the different conditions received 1) only correct solutions, 2) correct and erroneous examples, or 3) additional comparison prompts. Students who were prompted to compare erroneous solution attempts to correct solutions significantly outperformed their peers at posttest. Elaborating on errors seemed to mediate this effect. In accordance with the theoretical assumptions, the difference between conditions was only significant for students whose initial solution resembled the erroneous examples. Highlights: During problem solving, students tend to generate incorrect solution attempts. Subsequent prompts to compare incorrect and correct examples foster learning. Without comparison prompts, students almost exclusively refer to correct examples. Students benefit more from prompts if their attempts resemble the examples.